ANALISIS TINGKAT KEPUASAN PELANGGAN DENGAN MENGGUNAKAN KONSEP E-SERVQUAL (STUDI KASUS PELANGGAN SHOPEE) - Daryanti, Putri; Shihab, Muchsin Saggaff (Journal of Entrepreneurship, Management and Industry (JEMI), 2019)
The purpose of this study is to demonstrate the possible of importance-performacen analysis for decision making to assess importance of Shopee Company, an e-comerce company in delivering service quality. This study used a type of descriptive research with quantitative research methods. This study used a sample issued by 100 respondents, which were Shopee customers and had made transactions at least 2 times in the past 6 months. This study used E-SERVQUAL variables by analyzing data using the Importance Performance Analysis (IPA) method. The results were published in general indicate that the level of conformity was not good and has not reached the customer's needs. Four attributes needed to be improved, six attributes needed to be held, and four attributes that need to be reduced by priority are addressed in the Cartesian diagram of the Importance Performance Analysis (IPA)